2021
DOI: 10.1016/j.pmedr.2021.101459
|View full text |Cite
|
Sign up to set email alerts
|

Exploring hospital-based health information technology functions for patients with Alzheimer’s Disease and related Dementias

Abstract: Highlights: The study focused on five care coordination components of HIT among ADRD patients. HIT patient engagement linked to a significant reduction in preventable ED visits. Certain types of HIT are useful for reducing preventable EDs for ADRD patients. HIT can improve the wellbeing of ADRD patients especially during the COVID crisis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…For example, evidence has suggested that automatic notifications of ED visits, inpatient admissions, and discharges to primary care providers could reduce the risk of readmissions among Medicare fee-for-service (FFS) beneficiaries and encourage timely follow-ups 20. A recent study suggested that patients with ADRD treated in hospitals that utilized HIT care coordination and patient engagement services reported lower rates of preventable ED visits 21…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, evidence has suggested that automatic notifications of ED visits, inpatient admissions, and discharges to primary care providers could reduce the risk of readmissions among Medicare fee-for-service (FFS) beneficiaries and encourage timely follow-ups 20. A recent study suggested that patients with ADRD treated in hospitals that utilized HIT care coordination and patient engagement services reported lower rates of preventable ED visits 21…”
mentioning
confidence: 99%
“… 20 A recent study suggested that patients with ADRD treated in hospitals that utilized HIT care coordination and patient engagement services reported lower rates of preventable ED visits. 21 …”
mentioning
confidence: 99%
See 1 more Smart Citation